Associations between deprivation and rates of childhood overweight and obesity in England, 2007–2010: an ecological study. Issue 2 (13th April 2012) - Conrad, David; Capewell, Simon
Abstract : Objectives: To investigate the associations between deprivation and rates of childhood overweight and obesity in England, from 2007 to 2010. Design: An ecological study using routine data from the National Child Measurement Programme and Indices of Multiple Deprivation (IMD) 2010 scores. Setting: Local authority districts in England. Participants: Schoolchildren in Reception year (age 4–5 years) and Year 6 (age 10–11 years) attending non-specialist maintained state schools in England. Primary and secondary outcome measures: Prevalence of overweight in both Reception and Year 6, prevalence of obesity in both Reception and Year 6 and IMD 2010 scores for each local authority. Results: In 2009–2010, local authority IMD 2010 scores were strongly correlated with obesity rates among schoolchildren in Reception (r=0.625, p<0.001) and Year 6 (r=0.733, p<0.001). There were no statistically significant changes in association between obesity in Reception or Year 6 and IMD from 2007–2008 to 2009–2010. In contrast, the prevalence of overweight was not statistically significantly correlated with local authority IMD scores in Reception (r=0.095, p=0.092) and only weakly correlated in Year 6 (r=0.184, p=0.001). There were no statistically significant changes in association between overweight in Reception or Year 6 and IMD from 2007–2008 to 2009–2010. Conclusions: Childhood obesity rates in England are strongly associated with deprivation. Given the enormous public health implications of overweight and obesity in the population, these findings suggest that significant effort is required to tackle unhealthy weight in children in all local authorities and that this should be a priority in areas with high levels of deprivation.